2022
DOI: 10.1021/acsami.2c01208
|View full text |Cite
|
Sign up to set email alerts
|

Heterointerface and Defect Dual Engineering in a Superhydrophilic Ni2P/WO2.83 Microsphere for Boosting Alkaline Hydrogen Evolution Reaction at High Current Density

Abstract: Developing a high-performance electrocatalyst for hydrogen evolution reaction (HER) requires a comprehensive consideration of the three key factors, that is, intrinsic activity, electric conductivity, and active site number. Herein, we report the facile synthesis of a self-supported Ni2P/WO2.83 heterointerface microsphere as a highly active and low-cost catalyst for alkaline HER, which has simultaneously addressed these key issues by a joint application of heterointerface construction and defect and architectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…According to the Tafel plot fitted from the polarization curves (Figure b), the targeted catalyst showed a small Tafel slope with a value of 78 mV·dec –1 , which was similar to that of Pt/C (56 mV·dec –1 ) and lower than those of Ni 2 P/NF (106 mV·dec –1 ), V 2 O 3 /NF (112 mV·dec –1 ), Ni 3 V 2 O 8 /NF (116 mV·dec –1 ), and bare NF (159 mV·dec –1 ). Such fitted results suggested that the HER pathway over the series of catalysts should follow the Volmer–Heyrovsky mechanism with the Volmer step (H 2 O dissociation) as the rate-controlling step, and the smaller Tafel slope of Ni 2 P/V 2 O 3– x /NF catalyst implied an accelerated Volmer step by a rational combination of TMPs and defect-rich metal-oxides, which is in line with previous studies about concerted catalysts …”
Section: Results and Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…According to the Tafel plot fitted from the polarization curves (Figure b), the targeted catalyst showed a small Tafel slope with a value of 78 mV·dec –1 , which was similar to that of Pt/C (56 mV·dec –1 ) and lower than those of Ni 2 P/NF (106 mV·dec –1 ), V 2 O 3 /NF (112 mV·dec –1 ), Ni 3 V 2 O 8 /NF (116 mV·dec –1 ), and bare NF (159 mV·dec –1 ). Such fitted results suggested that the HER pathway over the series of catalysts should follow the Volmer–Heyrovsky mechanism with the Volmer step (H 2 O dissociation) as the rate-controlling step, and the smaller Tafel slope of Ni 2 P/V 2 O 3– x /NF catalyst implied an accelerated Volmer step by a rational combination of TMPs and defect-rich metal-oxides, which is in line with previous studies about concerted catalysts …”
Section: Results and Discussionsupporting
confidence: 89%
“…Such fitted results suggested that the HER pathway over the series of catalysts should follow the Volmer−Heyrovsky mechanism with the Volmer step (H 2 O dissociation) as the rate-controlling step, and the smaller Tafel slope of Ni 2 P/ V 2 O 3−x /NF catalyst implied an accelerated Volmer step by a rational combination of TMPs and defect-rich metal-oxides, which is in line with previous studies about concerted catalysts. 30 The aforementioned apparent HER performance may be overestimated because of the high specific surface area of nanomaterials. In an effort to accurately evaluate the intrinsic HER activity of the target catalyst, we further measured the electrochemical C dl of Ni 2 P/V 2 O 3−x /NF to calculate their ECSA and normalized the obtained current, particularly in comparison with that of V 2 O 3 /NF and Ni 2 P/NF catalysts.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations